Cigarette Smoking Does Not Affect Treatment Response to Tofacitinib in Rheumatoid Arthritis - Karatas, Ahmet; Oz, Burak; Dalkilic, Ediz; Can, Gercek; Pehlivan, Yavuz; Senel, Soner; Onen, Fatos (Wiley, 2018)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology (ACR) and Association-for-Rheumatology-Health-Professionals (ARHP) -- OCT 19-24, 2018 -- Chicago, IL